Bilateral Nephroureterectomy Versus Unilateral Nephroureterectomy for Treating De Novo Upper Tract Urothelial Carcinoma After Renal Transplantation: A Comparison of Surgical and Oncological outcomes. (August 2021) - Zhang, Qiming; Ma, Runzhuo; Li, Youzhao; Lu, Min; Zhang, Hongxian; Qiu, Min; Zhao, Lei; Zhang, Shudong; Huang, Yi; Hou, Xiaofei; Ma, Lulin
Background: There is currently no consensus on the optimal management of de novo unilateral upper tract urothelial carcinoma (UTUC) in renal transplant recipients. We aimed to compare the surgical and oncological outcomes of simultaneous bilateral radical nephroureterectomy (SBRNU) and unilateral radical nephroureterectomy (URNU) to determine the appropriate surgical method. Methods: Patients who developed de novo UTUC after renal transplantation and underwent surgical treatment at our center were included in the study. Outcomes were compared between the SBRNU group (underwent bilateral RNU within 3 months) and the URNU group using the Mann–Whitney U -test for continuous variables, Pearson's chi-square test for categorical variables, and the log-rank test for survival data. Results: A total of 48 patients were identified, including 21 and 27 patients in the SBRNU and URNU groups, respectively. Comparison of perioperative data showed that the SBRNU group had a significantly longer operative time ( P < .001) and hospital stay ( P = .040) than the URNU group but no statistically significant difference in the blood loss ( P = .171) and morbidity rate ( P = .798). After a median follow-up of 65 months, the SBRNU group had a significantly longer disease-free survival ( P = .009), longer cancer-specific survival ( P = .032), marginally longer overall survival ( P = .066), and similar intravesical recurrence-free survival ( P = .274) than the URNU group. Conclusions: Our data suggest that SBRNU contributes to improved survival without significantly compromising the perioperative outcomes compared with URNU. SBRNU can be considered a feasible option for de novo UTUC after renal transplantation in specialized centers. Prospective studies should be conducted to further explore the best treatment options for this group of patients.